PERSEBARAN DEBU TSP (TOTAL SUSPENDED PARTICULATE) TERHADAP KESEHATAN MASYARAKAT DI KAWASAN INDUSTRI PT SEMEN PADANG - Devi Maria Lumbantoruan; widya Prarikeslan (JURNAL BUANA, 2020)
The study of TSP dust Distribution (Total Suspendend Partikulate) on public health residing in the industrial area of PT Semen Padang. The purpose of this research, among others, to know: 1) spread of TSP dust to the health of people settled in the industrial area of PT Semen Padang spatial using ArcGis software. 2) Overview of the relationship between the health of disease in the community with TSP dust in Lubuk Kilangan Puskesmas. The methods used are quantitative descriptive analysis, spatial analysis and bivariate with SPSS 16.0 software. Spatial analysis with IDW analysis with the method of value ranges to know the hazard level in the location of the research point and the Buffer analysis to find out the radius of the TSP dust spread and the Bivariate analysis of Pearson correlation to describe to see what the correlation between x and Y variables is with the view of the test is significance correlation. The results of the study showed: 1). Spatial analysis acquired point location of SD N 20 Indarung is categorized as dangerous with a radius of 500 meters from the factory of PT Semen Padang the range 66-71 results of the monthly average TSP of 70.4444 μg/nm3 hr. The second point of the complex Unand D block in hazardous categories with a radius of 2000 meters from the cement plant, the result of the monthly average concentration is 69.1111 μg/nm3 hr. Point to three locations top of Bukit Hilalang Lubuk Kilangan in a very unhealthy category with a radius of 2000 meters. The average concentration is 65.4444 μg/nm3 HR, the range is 65-67. 2). The Correlation in the case of the ISPA in March 2019.899 means the perfect correlation relationship. The Sig. (2-tailed) amounted. 289 so H0 means that there is no link between the TSP dust and the case of ISPA in March 2019 is invalid data due to GIS. (2-tailed) the result > 0.05. While the relationship of TSP dust levels with ISPA case April Pearson Correlation is perfect. The results of the Sig. (2-tailed) p > 0.05 amounting to. 252. So H0 means there is no connection between the TSP dust and the ISPA case in April 2019.